EFFICIENCY OF ENTERPRISE COSTS MANAGEMENT IN MODERN СONDITIONS - N. V. Arsenieva; L. M. Putyatina; L. A. Uglova (Вестник университета)
The issues of improving enterprise cost management in modern conditions have been studied. Enterprise costs and product cost are the most important indicators that determine its financial results and the efficiency of economic activity in general. The effectiveness of cost management allows you to determine the reserves of their reduction and the possibility of intensive development. The main directions of analytical procedures for cost management and production cost have been considered. Production cost indicators have been analysed: cost of unit of goods, cost of all realized production, costs per one ruble of realized production and their change in time. The main factors that reduce the cost of production, which are generally divided into external and internal, have been assessed. Separate cost elements and possibilities of their decrease as well as reserves of cost management in perspective have been reviewed. The impact of inflation on the cost and prices of the enterprise’s manufactured products has been estimated, the main measures to improve cost management in order to increase the efficiency of the enterprise work have been given. The presented analysis is recommended for use at the machine-building industry enterprises, as well as at the enterprises that produce a wide range of products.